Model of a Pedagogical System for Developing Design Competence for Future Engineering using a Computer Grafika - Жавлонбек Зафаржонович Мадаминов (Researchparks Publishing, 2021)
The article describes the development and analysis of a pedagogical model for the development of engineers in the development of design competencies, the use of pedagogical systems and computer graphics, development using graphic programs, as well as in project processes, working drawings and assembly drawings.